OPTIMASI USULAN PERUBAHAN KAWASAN HUTAN DALAM RENCANA TATA RUANG WILAYAH PROVINSI (RTRWP) DI PROVINSI KALIMANTAN TIMUR - Donny Satria; Omo Rusdiana; Nining Puspaningsih (President University, 2017)
In 2009 the province of East Kalimantan submitted the proposed changes of forest area of ± 2.535.858 ha, however the recommended changes only ± 464.895 ha (18.33% of the proposal), according to the figure can be seen that there were significant gaps (differences) among the proposed changes with recommendations for forest areas changes that need to be optimized in any proposed changes of forest area by calculating the capacity of the environment in accordance to the Minister of Environment Regulation Number 17 of 2009 as well as spatial analysis. The purpose of this research was to determine land requirements, the effectiveness of land-use and forest areas that still have the potential for the proposed changes. Referring to the data processing, it was discovered that East Kalimantan Province in 2015 experienced the surplus of land availability of ± 1.374.046 ha and it was discovered that there are still non-productive land area of ± 2.774.571 ha. The results of the spatial data analysis suggests that changes of forest area can still be done in 8 districts/cities with a total area of ±132.578,57 ha.